Social workers' perceptions of their peers' unprofessional behavior. (May 2022) - Gricus, Michelle; Wysiekierski, Lili
Summary: This article explores social workers' perceptions of their colleagues' professional mistakes, and the influences of those opinions. Vignettes in a factorial survey helped to determine whether certain variables related to the social worker or the situation influenced the perception of others' professional errors and ethical violations. The changed variables included personal characteristics of the offending social worker such as perceived race, gender, and sexual orientation of the social worker, and characteristics of the situation, such as the length of time involved in unprofessional behavior. Findings: Licensed social workers in six U.S. states ( n = 5596) read vignettes based on real cases brought before licensing boards ( n = 22, 127) and assigned levels of seriousness and importance to discipline. The vignettes rated most highly involved perceived harm to a client or other vulnerable individual. Those on the lower end of seriousness and importance to discipline were those violations against the profession of social work. Analysis of changed variables indicated respondents' ratings were influenced by several situational factors, but not by personal characteristics of the social worker involved in the vignette. Applications: Our findings provide some insight into the decision-making factors important to social workers. The results may be helpful to licensing boards considering the contextual factors of unprofessional behavior and whether to discipline certain actions.